Effects of long-term dehydration on stress markers, blood parameters, and tissue morphology in the dromedary camel (Camelus dromedarius) - Ali, Mahmoud A.; Abu Damir, Hassan; Adem, Muna A.; Ali, Osman M.; Amir, Naheed; Shah, Asma A. M.; Al Muhairi, Salama S. M.; Al Abdouli, Khaled O. S.; Khawaja, Javed R.; Fagieri, Tareq A.; Adam, Abdelnasir; Elkhouly, Aboubakr A.; et al. (Frontiers in Veterinary Science, 2023)
Introduction Dromedary camels robustly withstand dehydration, and the rough desert environment but the adaptation mechanisms are not well understood. One of these mechanisms is that the dromedary camel increases its body temperature to reduce the process of evaporative cooling during the hot weather. Stress in general, has deleterious effects in the body. In this study, we sought to determine the effects of dehydration and rehydration on stress parameters in the dromedary camels and how it pacifies these effects. Methods Nineteen male camels were randomly divided into control, dehydrated and rehydrated groups, and fed alfalfa hay ad-libitum. The dehydrated and rehydrated groups were water-restricted for 20 days after which the rehydrated camels were provided with water for 72 h. The control and dehydrated camels were slaughtered at day 20 from the start of experiment whereas the rehydrated group was killed 72 h later. Many biochemical, hematological histopathological parameters and gene analysis were performed in relevant tissues collected including blood, plasma, and tissues. Results and discussion It was observed that severely dehydrated camels lost body weight, passed very hard feces, few drops of concentrated urine, and were slightly stressed as reflected behaviorally by loss of appetite. Physiologically, the stress of dehydration elicited modulation of plasma stress hormones for water preservation and energy supply. Our results showed significant increase in cortisol, norepinephrine and dopamine, and significant decrease in epinephrine and serotonin. The significant increase in malondialdehyde was accompanied with significant increase in antioxidants (glutathione, retinol, thiamin, tocopherol) to provide tissue protection from oxidative stress. The physiological blood changes observed during dehydration serve different purposes and were quickly restored to normality by rehydration. The dehydrated/rehydrated camels showed reduced hump size and serous atrophy of perirenal and epicardial fat. The latter changes were accompanied by significantly increased expression of genes encoding proteins for energy production (ANGPTL4, ACSBG1) from fat and significantly decreased expression of genes (THRSP; FADS 1&2) encoding proteins enhancing energy expenditure. This process is vital for camel survival in the desert. Dehydration induced no major effects in the vital organs. Only minor degenerative changes were observed in hepatic and renal cells, physiological cardiomyocyte hypertrophy in heart and follicular hyperplasia in splenic but lipidosis was not depicted in liver hepatocytes. Ketone bodies were not smelled in urine, sweat and breathing of dehydrated animals supporting the previous finding that the ß hydroxybutyrate dehydrogenase, a key enzyme in ketone body formation, is low in the camel liver and rumen. Rehydration restored most of blood and tissues to normal or near normal. In conclusion, camels are adapted to combat dehydration stress and anorexia by increasing anti-stressors and modulating genes involved in fat metabolism.